Affective State and the Encoding and Retrieval of Spatial Information from Campus Maps - Lokhande, Kiran J. (Tufts Archival Research Center, 2005)
While previous studies demonstrate some relationship between mood, arousal, and spatial memory, the exact mechanisms of local and global spatial perception remain unknown. Specifically, it is unclear whether the effects seen are caused by an allocation of visual attention towards the global or local elements of a stimulus, or whether the effect is due solely to organizational schemas created in memory. The present study manipulated arousal and mood to examine the role of visual attention and mental schemas in spatial memory. In the study, participants examined a college map while an eyetracker recorded their eye movements. Afterwards, they underwent free recall and spatial statement verification memory tests. Eyetracking results demonstrated that high arousal states cause participants to narrow their focus and produce smaller saccade amplitudes during study. However, memory test results found that participants under high arousal were able to more quickly recognize landmark relationships over long relative to short distances. The conflicting results show the role of both visual attention and mental schemas in spatial memory and has implications for the design of future research examining both factors.